Serum aspartate and alanine transaminase levels in workers exposed to lead - Waldron, H. A. (1964)
Serum aspartate and alanine transaminase levels were studied in a group of 46 workers exposed to lead. In none of them did the level of either enzyme vary from the values found in a group of 50 healthy persons with no industrial exposure to lead. No correlation was found between levels of aspartate transaminase or alanine transaminase and blood lead concentrations.